APPLICATION OF ANALYTICAL TOOLS FOR EVALUATING THR PERFORMANCE OF A MANUFACTURING ENTERPRISE - Levandovska, О. (Municipal economy of cities. Series: «Economy science», 2023)
The article focuses on the use of analytical tools, namely, methods of assessing the bankruptcy of an enterprise, developed by foreign authors. Calculations are made using various models, and it is proved that at the moment there is no "ideal" model that will take into account all the realities of the enterprise. The current unstable situation of Ukraine's economy, namely the full-scale invasion of the aggressor country by the Russian Federation, creates additional difficulties for enterprises for development and normal functioning, so the issue of timely performance assessment and efficiency forecasting is particularly acute. Analysis of recent research and publications. Today, there are many different publications on the topic of assessing the probability of bankruptcy, a significant number of authors are conducting various studies to identify the most reliable model for assessing the probability of bankruptcy from the models developed earlier by foreign scientists. And some experts studying this topic even offer their own methods. For example, the group of analysts O.Y. Bazilinska, T.G. Rzaeva, I.V. Stasiuk. Tereshchenko O.O. and others not only thoroughly analyzed the existing methods of assessing the probability of bankruptcy of an enterprise, but also presented a number of studies on the development of models for predicting the probability of bankruptcy in various sectors of the economy, such as construction, manufacturing and many others].Currently, a large number of different financial models have been developed that combine several different coefficients into one, resulting in a generalized assessment of the financial condition and determining the probability of bankruptcy. But the question arises, which method will really show the exact financial condition of the company and, moreover, give a forecast for the future? Therefore, the research topic is relevant. The problems of applying methods for diagnosing bankruptcy of an enterprise at the early stages are currently characterized as the most pressing issues of our time. The purpose of the article is to study the probability of bankruptcy of the manufacturing enterprise "X" on the basis of foreign forecasting methods.